Development and application of species ID and insecticide resistance assays, for monitoring sand fly Leishmania vectors in the Mediterranean basin and in the Middle East. - Sofia Balaska; Jahangir Khajehali; Konstantinos Mavridis; Mustafa Akiner; Kyriaki Maria Papapostolou; Latifa Remadi; Ilias Kioulos; Michail Miaoulis; Emmanouil Alexandros Fotakis; Alexandra Chaskopoulou; John Vontas (PLoS Neglected Tropical Diseases)
Background Development of insecticide resistance (IR) in sand fly populations is an issue of public health concern, threatening leishmaniasis mitigation efforts by insecticide-based vector control. There is a major knowledge gap in the IR status of wild populations worldwide, possibly attributed to the unavailability of specialized tools, such as bioassay protocols, species baseline susceptibility to insecticides and molecular markers, to monitor such phenomena in sand flies. Methodology/principal findings Sand fly populations from (semi-)rural regions of Greece, Turkey and Iran were sampled and identified to species, showing populations' structure in accordance with previously reported data. Genotyping of known pyrethroid resistance-associated loci revealed the occurrence of voltage-gated sodium channel (vgsc) mutations in all surveyed countries. Knock-down resistance (kdr) mutation L1014F was prevalent in Turkish regions and L1014F and L1014S were recorded for the first time in Iran, and in Turkey and Greece, respectively, yet in low frequencies. Moreover, CDC bottle bioassays against pyrethroids in mixed species populations from Greece indicated full susceptibility, using though the mosquito discriminating doses. In parallel, we established a novel individual bioassay protocol and applied it comparatively among distinct Phlebotomus species' populations, to detect any possible divergent species-specific response to insecticides. Indeed, a significantly different knock-down rate between P. simici and P. perfiliewi was observed upon exposure to deltamethrin. Conclusions/significance IR in sand flies is increasingly reported in leishmaniasis endemic regions, highlighting the necessity to generate additional monitoring tools, that could be implemented in relevant eco-epidemiological settings, in the context of IR management. Our molecular and phenotypic data add to the IR map in an area with otherwise limited data coverage.